INCREASING YIELD OF DISTILLATE FRACTIONS DURING COKING OF PETROLEUM RESIDUES - V. B. Terentyeva; А. I. Nikolaev; B. V. Peshnev (Тонкие химические технологии, 2019)
The research results of the influence of preliminary mechanochemical activation of heavy oil feedstock (oil-fuel, tar) on the output of their coking products are presented. Raw materials were activated by creating a cavitation effect when a hydrocarbon stream passes through a diffuser under a pressure. The pressure gradient on the diffuser ranged from 10 to 50 MPa, and the number of cycles of passage through the diffuser - from 1 to 5. It is shown that hydrodynamic cavitation processing results in a change in the physicochemical characteristics of heavy oil feedstock. The presented values of the raw material density and its fractional composition before and after processing suggest that the cavitation effect results in cracking reactions in the raw material. Changes in the characteristics of the raw material affect the change in the output of its coking products. It is established that as the pressure gradient and the number of impact acts increase, the yield of liquid coking products increases, and the yield of coke decreases. No relationship between the feedstock characteristics and the increase in the yield of distillate fractions as a result of prior cavitation effects has been established. At the same time, the preliminary mechanochemical activation of the raw materials leads to a decrease in the density and refractive index of the liquid coking products, a decrease in the temperature of their initial boiling point, and an increase in the content of hydrocarbons in the gasoline and kerosene fractions in them. The increase in the density and refractive index of the light fractions of the liquid coking products suggests that the aromatization process proceeds as a result of mechanochemical activation.